ACCOUNTING AND LEGAL ASPECTS OF BUDGET EXECUTION - Mihajlović, Milan; Damnjanović, Radovan; Savić, Aleksandar (International Journal of Economic Practice and Policy, 2024)
The economic and legal dimension of the budget has always attracted the attention of researchers, both because of its dispositiveness and because of the once necessary stochasticity. This way of its existence and the conditions of its existence are precisely the subject of this paper. The indispensable efficiency of the public sector and its driving force in the conditions of modern existence of the social community and the assumptions that limit its activities complicate the position of the budget and its basic prerogatives as can be seen in all modern states, including ours. Legal constraints on the one hand and economic constraints on the other place the budget in a position that exists continuously, adjusting to the input side conditioned by budget revenues and the output side conditioned by budget expenditures. In this regard, respect for budget procedures and normative structure makes the budget extremely important for the study. In order to complete the budget procedure, after the budget year, the final account is made, which shows the accounting discrepancies and deviations of the execution by the executive from the budget approved by the legislature.
Keywords: budget; principles; procedures; accounting system; public procurement; final account; control